Efek Sinergetik Ekstrak Daun Jambu Bol (Syzygium malaccense) dan Iodida terhadap Korosi Baja dalam Larutan Asam - Putri Untari (Universitas Jambi, Fakultas Sains dan Teknologi, Program Studi Kimia, 2020)
Research on the synergistic effect of jambu bol leaves extract and iodide on the corrosion of mild steel in acid solution has been carried out by weight loss, potentiodynamic polarization measurements, Fourier transform infrared (FTIR), scanning electron microscopy (SEM) analysis, and X-Ray Diffraction (XRD) characterization. The inhibition efficiency increased with increasing iodide concentration and temperature. The highest inhibition efficiency was 92.05% in inhibitor of 5 g / L jambu bol leaves extract with the addition of 0.08 g / L of iodide. Adsorption of jambu bol leaves extract and iodide following the Langmuir isotherm adsorption. Potentiodynamic polarization measurements show the combination of jambu bol leaves inhibitor and iodide was a type of mixture inhibitor in hydrochloric acid solution. The synergistic effect of guava bol extract and potassium iodide was studied using thermodynamic and kinetic parameters. Keywords: Jambu bol leaves, corrosion inhibitor, weight loss, synergistic effect, Langmuir isotherm